2011
DOI: 10.3892/ijmm.2011.808
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations of the VHL gene in seven Chinese families with von Hippel-Lindau disease

Abstract: Abstract. Von Hippel-Lindau (VHL) disease is a hereditary tumor syndrome caused by mutations or deletions within the VHL tumor-suppressor gene, but VHL germline mutations in the Chinese have rarely been studied. To investigate the genetic profile of VHL mutations in the Chinese population, we evaluated the clinical characteristics of seven Chinese families suffering from VHL disease and determined the particular germline mutations in their VHL genes. Direct sequencing and real-time quantitative PCR was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Currently, nine studies including the present study have been conducted on 77 Chinese families and have described 49 mutations of VHL . [ 19 20 21 22 23 24 25 26 27 ] The mutations were summarized according to the position, nucleotide change, effect on coding sequence, and associated VHL phenotype (s) [ Table 5 ]. Independent of phenotype, the most frequent mutations were p.S65W, p.N78S, p.R161Q and p.R167W.…”
Section: R Esultsmentioning
confidence: 99%
“…Currently, nine studies including the present study have been conducted on 77 Chinese families and have described 49 mutations of VHL . [ 19 20 21 22 23 24 25 26 27 ] The mutations were summarized according to the position, nucleotide change, effect on coding sequence, and associated VHL phenotype (s) [ Table 5 ]. Independent of phenotype, the most frequent mutations were p.S65W, p.N78S, p.R161Q and p.R167W.…”
Section: R Esultsmentioning
confidence: 99%
“…A total of 52 studies, assessing 840 participants with vHL type 2, provided information on the frequency of PPGL. Most of these studies were conducted in Europe ( n =18) ( 16 , 17 , 21 , 25 , 26 , 28 , 29 , 62 , 66 , 68 , 70 , 71 , 72 , 73 , 76 , 83 , 91 , 92 ), followed by Eastern Asia ( n =17) ( 35 , 36 , 40 , 44 , 45 , 47 , 48 , 74 , 75 , 77 , 78 , 79 , 80 , 81 , 82 , 86 , 87 ) and North America ( n =9) ( 53 , 59 , 60 , 61 , 63 , 64 , 65 , 69 , 84 ). All studies assessed patients of all age groups, with the mean onset age of PPGL being 28.8 years (as reported in 21 studies ( 21 , 26 , 35 , 40 , 44 , 47 , 55 , 59 , 60 , 61 , 65 , 67 , 71 , 72 , 74 , 77 , 79 , 85 , 86 , …”
Section: Resultsmentioning
confidence: 99%
“…All studies assessed patients of all age groups, with the mean onset age of PPGL being 28.8 years (as reported in 21 studies ( 21 , 26 , 35 , 40 , 44 , 47 , 55 , 59 , 60 , 61 , 65 , 67 , 71 , 72 , 74 , 77 , 79 , 85 , 86 , 87 , 88 )). Six studies reported a consecutive sample ( 16 , 17 , 29 , 66 , 77 , 78 ), whereas in 39 studies a convenience sample was assessed ( 21 , 25 , 35 , 45 , 47 , 53 , 56 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations